Analysis of Pantun in the Animated Film Upin & Ipin Episode "Pesta Pantun" and Its Implications in Learning Malay Culture for Junior High School Students in Riau - Giovannesandesva Hendri; Rizka Auliya Jufri; Hasnah Faizah (International Journal of Studies in International Education, 2026)
This study aims to analyze the structure, meaning, and values ​​of Malay culture in the animated film Upin & Ipin episode "Pesta Pantun", and its implications in learning for junior high school students in Riau. The method used is qualitative with a content analysis approach. The research data in the form of 19 pantuns were collected through listening and note-taking techniques, then analyzed based on the structure (sampiran and content), meaning, and cultural values. The results show that advice pantuns have a complete structure and function to convey moral values, humorous pantuns are flexible as a medium of entertainment, and riddle pantuns are relatively consistent and function to develop critical thinking skills. In terms of meaning, pantuns contain explicit and implicit messages that reflect the values ​​of politeness, togetherness, intelligence, and respect for Malay traditions. The implications of this study indicate that the use of animation media in pantun learning can increase student engagement and understanding contextually, so it is relevant to be applied to junior high school students in Riau.